Transplantation of Amniotic Membrane to the Subretinal Space in Pigs - Jens Folke Kiilgaard; Erik Scherfig; Jan Ulrik Prause; Morten la Cour (Stem Cells International)
Purpose. To investigate the effect of transplanted amniotic membrane (AM) on subretinal wound healing. Methods. Nine Danish Landrace pigs had surgical removal of retinal pigment epithelium (RPE) and mechanical damage of Bruch’s membrane (BM) and served as a control group. 15 pigs additionally had AM transplanted to the subretinal space. Results. AM significantly reduces choroidal neovascularisation when complete coverage of the induced defect is obtained (7 pigs) (P<0.05). In cases where AM did not cover the rupture in BM choroidal tissue covered the transplanted membrane (8 pigs). AM is well tolerated in the subretinal space, causes only limited inflammation, and is covered with a monolayer of pigmented cells when in contact with the host RPE. Conclusions. AM modifies choroidal neovascularisation after BM damage and may serve as a basement membrane substitute for the RPE.